xercises 8-13, identify the equations as linear, quadratic, or neither.8. 4 5x 09. 5x 2 010. 3x - 6x2 =011. 1 - x + 2x = 012. 7x4 8= 013. 3x+2= 0Objective 2: Zero Product Rule(s&opaFor Exercises 14-22, solve the equations using the zero product rule. (See Examples 1-3.)14. (x - 5) (x + 1)16. (3x 2)(3x + 2) 0bopuou15. (x 3)x 1) = 01017. (2x - 7)(2 + 7) = 018. 2x 7)(x 7) 019. 3(x+ 5)(x + 5) 020. (3x 2)(2x - 3) 021. x(5x - 1)00 (8 + xe)x "z123. For a quadratic equation of the form ax bx + c = 0, what must be done before applying the zeroproduct rule?24. What are the requirements needed to use the zero product rule to solve a quadratic equation or higherdegree polynomial equation?o 0Objective 3: Solving Equations by FactoringE017 D 1For Exercises 25-72, solve the equations. (See Examples 4-8.)P 13h27. z210z - 24 = 025. p2- 2p - 15 026. y2 - 7y - 8= 0TM S30. 4x2 11x = 31728. w2- 10w + 16 = 029. 2q 7q 433. 2k2 28k +96 = 031. 0=9x2-432. 4a 49 034. 0=2P+20r+ 5035. O =2m3 - 5m2 - 12m36. 3n 4n n = 0S039. x(x - 4)(2x +3) = 037. 5(3p+1)(p- 3)(p + 6) 038. 4(2x 1)(x - 10)(x + 7) = 03T3040. x(3x + 1)(x + 1) = 041. -5x(2x + 9)(x 11) 042. -3x(x + 7)(3x 5) = 043. x 16x = 044. t3- 36t= 045. 3x2 18x = 0O46. 2y2 20y 047. 16m2 =948. 9n2 1130YM49. 2y+ 14y2 -20y50. 3d3 6d2 = 24d51. 5t 2(t-7) = 052. 8h 5(h-9)+653. 2c(c 8)- 3054. 3q(g 3) 12=55. b3 = -4b2 -4b56. x36x12x257. 3(a2a)= 2a- 9

Question
Asked Nov 24, 2019
2 views

I did this one #27

xercises 8-13, identify the equations as linear, quadratic, or neither.
8. 4 5x 0
9. 5x 2 0
10. 3x - 6x2 =
0
11. 1 - x + 2x = 0
12. 7x4 8= 0
13. 3x+2= 0
Objective 2: Zero Product Rule
(s&opa
For Exercises 14-22, solve the equations using the zero product rule. (See Examples 1-3.)
14. (x - 5) (x + 1)
16. (3x 2)(3x + 2) 0
bopuou
15. (x 3)x 1) = 0
1
0
17. (2x - 7)(2 + 7) = 0
18. 2x 7)(x 7) 0
19. 3(x+ 5)(x + 5) 0
20. (3x 2)(2x - 3) 0
21. x(5x - 1)0
0 (8 + xe)x "z
1
23. For a quadratic equation of the form ax bx + c = 0, what must be done before applying the zero
product rule?
24. What are the requirements needed to use the zero product rule to solve a quadratic equation or higher
degree polynomial equation?
o 0
Objective 3: Solving Equations by Factoring
E0
17 D 1
For Exercises 25-72, solve the equations. (See Examples 4-8.)
P 13h
27. z210z - 24 = 0
25. p2- 2p - 15 0
26. y2 - 7y - 8= 0
TM S
30. 4x2 11x = 3
17
28. w2- 10w + 16 = 0
29. 2q 7q 4
33. 2k2 28k +96 = 0
31. 0=9x2-4
32. 4a 49 0
34. 0=2P+20r+ 50
35. O =2m3 - 5m2 - 12m
36. 3n 4n n = 0
S0
39. x(x - 4)(2x +3) = 0
37. 5(3p+1)(p- 3)(p + 6) 0
38. 4(2x 1)(x - 10)(x + 7) = 0
3T
30
40. x(3x + 1)(x + 1) = 0
41. -5x(2x + 9)(x 11) 0
42. -3x(x + 7)(3x 5) = 0
43. x 16x = 0
44. t3- 36t= 0
45. 3x2 18x = 0
O
46. 2y2 20y 0
47. 16m2 =9
48. 9n2 1
1
30YM
49. 2y+ 14y2 -20y
50. 3d3 6d2 = 24d
51. 5t 2(t-7) = 0
52. 8h 5(h-9)+6
53. 2c(c 8)
- 30
54. 3q(g 3) 12
=
55. b3 = -4b2 -4b
56. x36x12x2
57. 3(a2a)= 2a- 9
help_outline

Image Transcriptionclose

xercises 8-13, identify the equations as linear, quadratic, or neither. 8. 4 5x 0 9. 5x 2 0 10. 3x - 6x2 = 0 11. 1 - x + 2x = 0 12. 7x4 8= 0 13. 3x+2= 0 Objective 2: Zero Product Rule (s&opa For Exercises 14-22, solve the equations using the zero product rule. (See Examples 1-3.) 14. (x - 5) (x + 1) 16. (3x 2)(3x + 2) 0 bopuou 15. (x 3)x 1) = 0 1 0 17. (2x - 7)(2 + 7) = 0 18. 2x 7)(x 7) 0 19. 3(x+ 5)(x + 5) 0 20. (3x 2)(2x - 3) 0 21. x(5x - 1)0 0 (8 + xe)x "z 1 23. For a quadratic equation of the form ax bx + c = 0, what must be done before applying the zero product rule? 24. What are the requirements needed to use the zero product rule to solve a quadratic equation or higher degree polynomial equation? o 0 Objective 3: Solving Equations by Factoring E0 17 D 1 For Exercises 25-72, solve the equations. (See Examples 4-8.) P 13h 27. z210z - 24 = 0 25. p2- 2p - 15 0 26. y2 - 7y - 8= 0 TM S 30. 4x2 11x = 3 17 28. w2- 10w + 16 = 0 29. 2q 7q 4 33. 2k2 28k +96 = 0 31. 0=9x2-4 32. 4a 49 0 34. 0=2P+20r+ 50 35. O =2m3 - 5m2 - 12m 36. 3n 4n n = 0 S0 39. x(x - 4)(2x +3) = 0 37. 5(3p+1)(p- 3)(p + 6) 0 38. 4(2x 1)(x - 10)(x + 7) = 0 3T 30 40. x(3x + 1)(x + 1) = 0 41. -5x(2x + 9)(x 11) 0 42. -3x(x + 7)(3x 5) = 0 43. x 16x = 0 44. t3- 36t= 0 45. 3x2 18x = 0 O 46. 2y2 20y 0 47. 16m2 =9 48. 9n2 1 1 30YM 49. 2y+ 14y2 -20y 50. 3d3 6d2 = 24d 51. 5t 2(t-7) = 0 52. 8h 5(h-9)+6 53. 2c(c 8) - 30 54. 3q(g 3) 12 = 55. b3 = -4b2 -4b 56. x36x12x2 57. 3(a2a)= 2a- 9

fullscreen
check_circle

Expert Answer

Step 1

consider the given quadratic equation

help_outline

Image Transcriptionclose

z10z-24 0

fullscreen
Step 2

Now making the factor of thi...

help_outline

Image Transcriptionclose

z10z 24= 0 z22 2z 24 0 z(z+12)-2(z+12)= 0 (z+12) (z-2) 0

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra

Other